Kinetics Modelling of Tributyltin Toxicity on The Growth of Bacillus subtilis - Abubakar, Abdussamad (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
growth of bacteria. In 2003, the Marine Environmental Protection Committee (MEPC) proposed that TBT be banned internationally due to the negative environmental impacts of the substance. However, even though BTs are banned, they may be found in large quantities in seawater, bottom sediments, and the biota, all of which are contaminated with them. To prevent the adhesion of fouling organisms to the surface of ships and boats, tributyltin (TBT) has been widely employed as an antifouling agent in marine paints for many years. Tributyltin has been discovered to be very persistent, particularly in sediment, and to be extremely harmful to species other than those targeted. Bacillus subtilis growth was intensely inhibited by tributyltin (TBT). As the TBT concentration increases, the overall specific growth rate was inhibited. The growth rates obtained were then modelled according to the modified Han-Levenspiel, Amor, Wang, Liu, Shukor and modified Andrews. Among the five models, the Andrew and Amor models show poor fittings. Results of the statistical analysis showed that the Shukor model was the best model based on the lowest values for RMSE and AICc, highest adjusted correlation coefficient (AdR2) and values of AF and BF closest to unity. The parameters obtained from the Shukor model were Ccrit 742.32 nM (95%, C.I., 303.35 to 1181.29), Î¼max 1.20 h-1 (95% C.I., 1.08 to 1.319) and m 0.507 (95% C.I., 0.308 to 0.832). The findings of this study can be utilized for further bioremediation works.